Preparation of ZnO/CuO under the regulation of SDS and its application in photocatalytic degradation (Indian Journal of Chemistry (IJC), 2024)
As a green and efficient treatment technology, photocatalysis has enormous advantages in degrading organic pollutants in water. Here, zinc acetate, copper acetate, and sodium hydroxide were used as raw materials to prepare ZnO/CuO composites under the mediation of sodium dodecyl sulfate (SDS). The structures and morphologies of desired products were characterized by X-ray powder diffraction (XRD) and scanning electron microscopy (SEM), respectively. The obtained samples used photo-catalysts to degrade the simulated pollutant of methylene blue (MB). The results showed that the crystals of ZnO and CuO were successfully produced with the co-precipitation method. Because of the regulation of SDS, the particles have high dispersibility and small particle sizes. Through photocatalytic performances, it was concluded that the degradation rate of the ZnO/CuO composite was higher than the corresponding monomers. It indicated that the synergistic effect of ZnO and CuO enhanced the photocatalytic degradation ability of ZnO/CuO composite, providing a potential application prospect for the development of efficient photocatalysts for environmental governance.